DEVELOPING ANIMATED VIDEO-BASED ENGLISH LEARNING MEDIA FOR SENIOR HIGH SCHOOL STUDENTS’ SPEAKING SKILLS: AN R&D STUDY USING A MODIFIED ADDIE MODEL WITH EXPERT VALIDATION AND SMALL-SCALE TRIAL AT SMA NEGERI 1 KABILA - Gunawan Gunawan; Harni Jusuf; Adimawati Helingo; Yuwin Rustam Saleh; Enni Akhmad (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
This study addresses the challenges faced by senior high school students in developing speaking skills in English as a Foreign Language (EFL), including limited vocabulary, pronunciation difficulties, low confidence, and the use of less engaging instructional media. The study aimed to develop and validate animated video-based English learning media to support students’ speaking skills. It employed a Research and Development (R&D) design using a modified ADDIE model limited to the Analyze, Design, and Develop stages and was conducted at SMA Negeri 1 Kabila during the 2025/2026 academic year. The needs analysis involved interviews with an English teacher and questionnaires administered to Grade X students. The developed 2D animated videos were validated by three media experts and three language experts using structured validation instruments. Feasibility was determined using percentage-based criteria, in which scores above 61% were categorized as feasible and scores above 81% as very feasible. The results showed that the media expert validation reached an average score of 82.18% (very feasible), while language expert validation reached 90% (very feasible), indicating high validity and appropriateness. A small-scale trial involving six students produced an average response above 90%, reflecting strong attractiveness, clarity, and motivational value. These findings suggest that the developed animated video-based media are valid and feasible for supporting speaking instruction at the senior high school level. However, this study was limited to validation and small-scale testing; therefore, future research should conduct large-scale implementation and experimental studies to examine the effectiveness of the media in improving students’ speaking performance.